Collaborative learning with Web 2.0 tools: analysing Malaysian students’ perceptions and peer interaction - Leow, Fui-Theng; Neo, Mai (Taylor & Francis, 2015)
Today, ICT, web resources and multimedia contents have become prevalent in Malaysian university classrooms; hence, the learning approaches need to be redesigned for enabling students to use these technologies in co-constructing new meaning. This study analyses student’s perception and their peer interaction in the constructivist–collaborative learning environment (CCLE) with multimedia contents and Web 2.0 tools, to address the research question: What is the impact of CCLE on student learning process? By using factor analysis on the questionnaire results, and applying content analysis on students’ comments in Web 2.0 tools and feedback given by 182 students at INTI International University, several components of constructivist–collaborative learning were identified. The discussion in this study focuses on “team” and its sub-components include group dynamics, students’ prior knowledge with team and group processing. The discussion provides more understanding on the impact on student learning process for enhancing the learning experiences in Malaysian university class environment.